KONSISTENSI HASBI ASH-SHIDDIEQY TENTANG KEHUJJAHAN HADIS: STUDI KASUS HADIS-HADIS DAIF DALAM TAFSIR AN-NUR - Ashwarina, Ashwarina; Safri, Edi; Wendry, Novizal (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
The problem in this research is how the attitude of Hasbi Ash-Shiddieqy towards the hadith daif and what are the implications of the inclusion of the hadith in the Tafsir An-Nur. The objectives to be achieved in this research are: (1) to find out how Hasbi Ash- Shiddieqy's attitude towards the hadith daif. (2) to trace whether the daif hadith in Tafsir An-Nur was used as evidence in interpreting a verse, especially verses of law. (3) to find out the implications of the inclusion of the daif hadith in the Tafsir An-Nur. This research is in the style of library research, while the primary data source is Tafsir An-Nur by Hasbi Ash-Shiddieqy and supporting sources in the form of tafsir books and other hadiths. The method used is literature and documentary studies, while the data analysis uses descriptive analysis. The results of this study reveal several findings about the consistency of Hasbi Ash-Shiddieqy regarding the authenticity of hadith, namely: (1) Hasbi Ash-Shiddieqy's attitude towards daif hadith, seen Hasbi's inconsistency between theory and practice of using daif hadith. (2) The daif traditions in An-Nur's interpretation are generally not used as evidence in interpreting a verse, especially law verses, because the traditions are presented only as explaining asbabul nuzul ayat, additional information in interpreting a verse. (3) The implication of the inclusion of daif hadith in An-Nur's interpretation has several forms, namely Hasbi uses the dha'if traditions in An-Nur's Tafsir, even uses mawdhu 'hadiths or narrations that have mawdhu characteristics, then regarding how to quote the hadith which Without explaining the mukharij or the companions who narrated the hadith, to make matters worse Hasbi included the hadith with the Indonesian editorial staff, even without including the mukharij or the narrators of the hadith, the inconsistency also for Hasbi was the use of hadith source books not from hadith books. Therefore, it is necessary to refill the hadiths in the Tafsir An-Nur book.